PENGARUH BI 7-DAY REPO RATE, CAR, BOPO, DAN DPK TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2019 - Ida Sholichatunnisa; Mariana Mariana (Jurnal Bina Akuntansi, 2022)
This study aims to determine the effect of the BI 7-Day Repo Rate, Capital Adequacy Ratio (CAR), Operational Costs on Operating Income, Third Party Funds (TPF) on the profitability of Islamic Commercial Banks in Indonesia for the period 2015 to 2019. This study uses secondary data sources. obtained from the financial statements of each Islamic Commercial Bank that has been registered with the Financial Services Authority (OJK) from 2015 to 2019. The sample used in this study was 12 Islamic Commercial Banks using the purposive sampling method. The data analysis technique in this study uses multiple linear analysis techniques. The results of this test indicate that the BI 7-Day Repo Rate, CAR, and TPF partially have no effect on profitability, while OEOI has an effect on profitability. BI 7-Day Repo Rate, CAR, BOPO, and TPF simultaneously have an influence on the profitability of Islamic Commercial Banks.